2021
DOI: 10.21315/mjms2021.28.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Virus Infection and Its Associated Factors Among Blood Donors in Yemen

Abstract: Background: In limited-resource countries, the prevalence of hepatitis B virus (HBV) infection can be measured using data taken from blood donors. This study aimed to determine the HBV infection seroprevalence and its associated factors among blood donors in Sana’a Governorate, Yemen. Methods: A cross-sectional study was conducted on 500 people who donated blood at hospitals located in Sana’a between August and October 2016. The volunteers were aged 18–65 years old and were recruited using convenience sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
2
0
0
Order By: Relevance
“…The overall prevalence rate (2.4%) of HBsAg among blood donors in this study was analogous to the studies carried out in various locations such as Yemen (2.6%), 17 Ethiopia (2.6%), 18 and India (2.12%). 19 However, the seropositivity rate of the present study was higher than our previous study (1.9%).…”
Section: Discussionsupporting
confidence: 84%
“…The overall prevalence rate (2.4%) of HBsAg among blood donors in this study was analogous to the studies carried out in various locations such as Yemen (2.6%), 17 Ethiopia (2.6%), 18 and India (2.12%). 19 However, the seropositivity rate of the present study was higher than our previous study (1.9%).…”
Section: Discussionsupporting
confidence: 84%
“…The married group had higher chance for acquiring hepatitis Viruses from their partners. This was also supported by the study conducted in Yemen [39], which revealed high prevalence of HBsAg in married blood donors.…”
Section: Discussionsupporting
confidence: 66%